2022
DOI: 10.3390/math10162962
|View full text |Cite
|
Sign up to set email alerts
|

Infinite-Server Resource Queueing Systems with Different Types of Markov-Modulated Poisson Process and Renewal Arrivals

Abstract: In this paper, we propose models that significantly expand the scope of practical applications, namely, queueing systems with various nodes for processing heterogeneous data that require arbitrary resource capacities for their service. When a customer arrives in the system, the customer typeis randomly selected according to a set of probabilities. Then the customer goes to the server of the corresponding device type, where its service is performed during a random time period with a distribution function depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…On the other hand, controversial points have been identified. For example, there is a contradiction in the approaches of some authors: E. Pankratova et al propose a mass service model with an unlimited number of servers [17], and Hao and Yifei are based on the idea that it is economically inexpedient to open a large number of servers [21]; in optimization issues, scientists rely on the development of alternative hypotheses and models [22], which is not always able to reflect the single best solution; and in the context of forecasting, a number of alternative prediction methods should be applied rather than limiting to comparing only two different models, as was conducted in May et al [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, controversial points have been identified. For example, there is a contradiction in the approaches of some authors: E. Pankratova et al propose a mass service model with an unlimited number of servers [17], and Hao and Yifei are based on the idea that it is economically inexpedient to open a large number of servers [21]; in optimization issues, scientists rely on the development of alternative hypotheses and models [22], which is not always able to reflect the single best solution; and in the context of forecasting, a number of alternative prediction methods should be applied rather than limiting to comparing only two different models, as was conducted in May et al [41].…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have revealed the following regularity: the optimal number of server resources has the highest value for the first case and the lowest for the third model [16]. In the example of heterogeneous resource-based mass service systems, Pankratova et al offer a method for determining the optimal level of resource provision for the k-th channel of the system [17]:…”
Section: Optimization Of Technical Resourcesmentioning
confidence: 99%
“…Suppose that one chooses the departure epochs to study the customer process in view of the Poisson arrivals assumption employed and upon departures from both cashiers in view of varying work rates, then the PASTA principle holds good. By the arguments in [21][22], the customer process described above forms an irreducible and aperiodic Markov chain as time grows large. Again, the time process becomes a stationary process as time grows large [23][24].…”
Section: Modeling and Methodsmentioning
confidence: 99%
“…Efrosinin and Sctrik [20,21] showed that, in an M/M/K queue, the optimal threshold levels may also depend on the states of slower servers; however, this influence is negligible. In [22], a finite-source queueing system serving one class of customers and consisting of heterogeneous servers with unequal service intensities and of one common queue were investigated. The authors of [23] provided an analysis of the dependence of the convergence of experimental results on the type of distribution used by the system parameters in heterogeneous queueing resource system with an unlimited number.…”
Section: Introductionmentioning
confidence: 99%